Pengaruh Konsentrasi Kepemilikan, Ukuran Dewan Komisaris, Ukuran Komite Audit, Reputasi Kantor Akuntan Publik Terhadap Intellectual Capital Disclosure - Sarah Nurjanah; Dirvi Surya Abbas; Hamdani Hamdani (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
Intellectual capital disclosure in Indonesia is still voluntary so that intellectual capital is rarely disclosed by companies. The purpose of this study is to determine the effect of ownership concentration, the size of the Board of Commissioners, the size of the Audit Committee, the reputation of the Public Accounting Firm on intellectual capital in banking companies listed on the Indonesia Stock Exchange in the 2016-2020 period.. Using purposive sampling as a technique for sampling. Based on the established criteria, 10 companies were obtained as samples. The type of data used is secondary data obtained from the financial statements of banking companies listed on the IDX. The analysis technique uses Moderated Regression. The results of the concentration of ownership, the size of the Board of Commissioners, the size of the Audit Committee, the reputation of the Public Accounting Firm have an effect on intellectual capital disclosure.